A NEW COELACANTH SPECIMEN WITH ELONGATE RIBS FROM THE MIDDLE TRIASSIC (LADINIAN) KALKSCHIEFERZONE OF MONTE SAN GIORGIO (CANTON TICINO, SWITZERLAND) - SILVIO RENESTO; FABIO MAGNANI; RUDOLF STOCKAR (Rivista Italiana di Paleontologia e Stratigrafia, 2021)
A new finding of a coelacanth from the upper Ladinian upper Kalkschieferzone of the Meride Limestone Formation of Monte San Giorgio (UNESCO World Heritage area) is described. It represents the first known coelacanth from the Middle Triassic that undoubtedly bears elongate thin ribs. The incompleteness of the specimen prevents a reliable taxonomic assignment or the erection of a new species, however some characters, mainly scale morphology, are very similar to those of the holotype of Heptanema paradoxum Bellotti, 1857 from the roughly coeval Perledo Formation of Northern Italy. Elongate ribs are not reported in original descriptions of H. paradoxum, however small portion of ribs are visible among the scales of the holotype. Accordingly, the new specimen is tentatively ascribed to Heptanema as Heptanema cf H. paradoxum.